About the Xiongnu aristocratic tomb: structures, findings, associated chronology, evolution and changes - Gelegdorj Eregzen (Археология евразийских степей)
Almost 100 years have passed since the first excavations of the Xiongnu noble tombs by the expedition of P.K. Kozlov in the Noin-Ula Mountains. Since then, 13 archaeological sites of the Xiongnu elites have been discovered and in 4 places excavations have not yet been carried out, such as Borbulag, Khyalganat, Ovoono Khar and Orgoiton, and in the rest, research work was carried out. At present, a total of 28 Xiongnu elite tombs have been excavated in Mongolia, Baikal and Tuva. Research work is also being carried out in 4 places, such as Noin-Ula, Duurlig Nars, Gol mod-II and Belkhin am. This article discusses the structural features of the tombs and the relationship of the discovered artifacts, the results of radiocarbon analysis, the date range of the tombs and the circumstances of the creation of large square-shaped tombs for the Xiongnu elites. In other words, this article is intended to raise the question of the evolution of large tombs of the highest rank of the Xiongnu.